Stabilization expansive clayey with nano-lime to reduce environmental impact - Firoozia, Ali Akbar; Naji, Maryam; Firoozi, Ali Asghar (Penerbit Universiti Kebangsaan Malaysia, 2022)
For years, geotechnical engineers have been concerned about expansive soils. Expansive soils are characterized by large volumetric changes related to variations in moisture content. Variations in soil water content may take place naturally during seasonal changes or maybe manmade caused by dewatering activities. The quantity of shrinkage and swell is influenced by numerous parameters, including the quantity of minerals clay in the soil, moisture content, dry density, and climate change. In most countries, numerous structures, including pavements and buildings, are damaged as a result of this shrinkage/swelling. Several ground improvement techniques are available for stabilizing expansive soil to modify its engineering performance. These methods include soil replacement, mixing with chemical additives, and soil reinforcement. The present study expressions the effect of nano-lime (i.e., 0.1, 0.3, 0.5, 0.7, 1.0, 2.0 and 3.0%), and lime (1, 3, 5, 8, and 10%), as chemical additive to improve clayey soil (i.e., illite and kaolinite). The effect of nano-lime and lime were investigated using Atterberg’s limits tests. The Atterberg limits were screening significant changes in the proportion of additional nano-lime and lime. The results show that less amount of nano-lime (1% and 2% for illite and kaolinite respectively) decreased the plastic limit, while for lime it was reported 8% for illite and 5% for kaolinite respectively. In conclusion, less quantity of nano-lime (1-2%) is able to improve soil parameters.